2012
DOI: 10.4028/www.scientific.net/amm.232.106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Delamination in Drilling Rice Husk Reinforced Polyester Composites

Abstract: Delamination is recognized as one of the most critical defects that can result from the machining composites. Delamination has been a major form of failure in drilled composite materials due to the composites lack of strength in the drilling direction, which results in poor surface finish, reduction in bearing strength, reduction in structural integrity and ultimately poor performance of the composite. Currently, most of the major research reported delamination address specific of machining fiber glass, graphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Although it has been found that the HSS twist drill is not compatible with drilling of glass and carbon fiber reinforced composites, 30,31 the results of current research reveal that the HSS twist drill is compatible for drilling of jute fiber reinforced composite laminates. This conclusion agrees with the results of 10,32 during drilling of NFCs. This simply indicates that the drill geometry which is suitable for drilling of special composite laminate may not be compatible with other type of laminates.…”
Section: Resultssupporting
confidence: 92%
“…Although it has been found that the HSS twist drill is not compatible with drilling of glass and carbon fiber reinforced composites, 30,31 the results of current research reveal that the HSS twist drill is compatible for drilling of jute fiber reinforced composite laminates. This conclusion agrees with the results of 10,32 during drilling of NFCs. This simply indicates that the drill geometry which is suitable for drilling of special composite laminate may not be compatible with other type of laminates.…”
Section: Resultssupporting
confidence: 92%
“…In the course of the drilling machining operation of rice husk reinforced polyester composites, brad drill caused higher delamination values compared to twist and end mill drill, while an increase in delamination when feed rate and spindle speed are increasing [77]. Rice husk reinforced polyester composites delamination value is lower than the glass fiber reinforced polymer [77]. Also, a twist 118°d rill gives good results in terms of delamination minimization because of a bigger point angle and is well adapted for metal drilling [77].…”
Section: Delaminationmentioning
confidence: 98%
“…104 Some of the tools materials and their geometry affecting the performance of the NFRC are shown in Table 4. [105][106][107][108][109][110][111][112][113][114][115][116][117] The above literature discussed and produced the full information about the parameters such as delamination, torque and trust force which affected the performance of the NFRC. The composite's machining can be broadened by introducing other effective natural fibers that can be surveyed based on their mechanical properties, fiber orientation, and machining ability.…”
Section: Effect Of Drilling On Different Characteristicsmentioning
confidence: 99%